Anthropocentrism of Encyclical Laudato Si’ - Łepko, Zbigniew (Studia Ecologiae et Bioethicae, 2017)
The article points to anthropocentrism as one of the main categories of the encyclical Laudato Si’. It is, therefore, the key to the proper understanding and reception of the encyclical’s message. This concept also defines the position of Pope Francis in today’s dispute related to identifying the causes behind the crisis of modern civilization which finds its expression, among others, in the environmental crisis. Although the Pope associates its cause with tyrannical or distorted anthropocentrism, he does not juxtapose it with biocentrism, but rather, with appropriate anthropocentrism. Such anthropocentrism is an expression of proper anthropology, which is the basis of appropriate ecology.